Planificación de un sistema de gestión de la calidad como plataforma para integrar otros modelos de gestión (2012)
The implementation of several standard management systems, in the same organization, poses administrative, technical and human challenges in order to achieve an integrated, harmonious and effective management system.Empirically it is generally considered that the quality management system, which is directly related to meeting the client’s expectations, should serve as a basic platform for the easy integration of other management systems.This article presents the results of an investigation conducted in order to examine how to plan the quality management system, so as to facilitate the integration of other management systems. To this end, an extensive search of literature and in-depth interviews were conducted with Consultants, Coordinator’s management systems, graduate students whose academic work had been the integration of management systems, internal and external auditors of management systems, Managers, Leaders, processers and researchers in the field of integration.We determined the impact on the organizations which have a quality management system, when you want to implement another standardized management model, we examined how the implementation methodologies are followed, the recommendations that should be taken into account for the definition of a quality management system, the usefulness for business of management systems and what integration means.Based on this information we propose a planning methodology that plots the quality management system on a platform for the integration of other management models.